Cellular and Molecular Mechanism of Traditional Chinese Medicine on Ventricular Remodeling - Zhu, Yong-Chun; Liang, Bo; Gu, Ning (Frontiers in Cardiovascular Medicine, 2021)
Ventricular remodeling is related to the renin-angiotensin-aldosterone system, immune system, and various cytokines involved in inflammation, apoptosis, and cell signal regulation. Accumulated studies have shown that traditional Chinese medicine can significantly inhibit the process of ventricular remodeling, which may be related to the mechanism mentioned above. Here, we conducted a system overview to critically review the cellular and molecular mechanism of traditional Chinese medicine on ventricular remodeling. We mainly searched PubMed for basic research about the anti-ventricular remodeling of traditional Chinese medicine in 5 recent years, and then objectively summarized these researches. We included more than 25 kinds of Chinese herbal medicines including Qiliqiangxin, QiShenYiQi Pill, Xin-Ji-Er-Kang formula, Yi Qi Wen Yang decoction, and found that they can inhibit ventricular remodeling effectively through multi-components and multi-action targets, which are promoting the clinical application of traditional Chinese medicine.